2021
DOI: 10.1206/0003-0090.446.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, Classification, Mesozoic Fossils, and Biogeography of the Leiinae (Diptera: Mycetophilidae)

Abstract: The relationships among the genera of fungus gnats in the mycetophilid subfamily Leiinae are unclear, and the monophyly of this group is questionable. This monograph provides an extensive phylogenetic study of the Leiinae based on morphological data from a large taxonomic sample, including all genera that have ever been assigned to the subfamily and a wide outgroup sampling to properly test subfamilial monophyly. A data matrix with 128 morphological features of 117 terminal taxa was carried out under parsimony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 90 publications
2
32
0
Order By: Relevance
“…Cretomanota gondwanica (herein described), Alavamanota hispanica Blagoderov and Arillo, 2002 (Early Aptian–Middle Albian, Spain—Alonso et al., 2000) and A. burmitina Blagoderov and Grimaldi, 2004 (Cenomanian, Myanmar—Shi et al., 2012) were added to the data matrix used in Oliveira and Amorim (2021) as new terminal taxa. That is the most updated and comprehensive study of the internal relationships of the subfamily Leiinae.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cretomanota gondwanica (herein described), Alavamanota hispanica Blagoderov and Arillo, 2002 (Early Aptian–Middle Albian, Spain—Alonso et al., 2000) and A. burmitina Blagoderov and Grimaldi, 2004 (Cenomanian, Myanmar—Shi et al., 2012) were added to the data matrix used in Oliveira and Amorim (2021) as new terminal taxa. That is the most updated and comprehensive study of the internal relationships of the subfamily Leiinae.…”
Section: Methodsmentioning
confidence: 99%
“…The Mycetophilidae (extant representatives are shown in Figs 1a, b, and c) include over 4200 described extant species in almost 150 genera, distributed in six subfamilies—Sciophilinae, Tetragoneurinae, Leiinae, Gnoristinae, Mycomyiinae and Mycetophilinae (Oliveira and Amorim, 2021). Although many of the genera in the family are worldwide in distribution, the generic composition of the family in tropical and temperate environments is remarkably different.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are more studies with the fauna of temperate regions, despite the fact that mycetophilids are more diverse in tropical areas, especially in the Neotropical region, where there are especially in the Neotropical region, where there are 1,202 species and 55 genera (Oliveira & Amorim, 2014;Amaral et al, 2022). Currently, the Mycetophilidae are divided into six subfamilies (Oliveira & Amorim, 2021) Scatopsidae (Fig. 3F).…”
Section: Genus Xenoplatyura Malloch 1928mentioning
confidence: 99%
“…Having been classified traditionally within the subfamily Leiinae (or the tribus Leiini) by earlier authors [1][2][3], molecular studies have instead suggested it belongs to Gnoristinae [4,5]. However, in a recent synopsis of Leiinae by Oliveira and Amorim [6], a new subfamily Tetragoneurinae was established, consisting of four genera including Docosia. Intrageneric phylogeny based on five molecular markers has been proposed by Ševčík et al [7].…”
Section: Introductionmentioning
confidence: 99%